Consortium Blockchain Consensus Algorithm Based on PBFT - Zhou, Yi-Hua; Fang, Jia-Bo; Jia, Yu-Xin; Jia, Li-Yuan; Shi, Wei-Min (Ji suan ji ke xue, 2021)
Aiming at the problems of poor scalability, random selection of master nodes, and high network overhead in the practical Byzantine (PBFT) consensus algorithm, the paper designs and proposes an optimized practical Byzantine consensus algorithm for the alliance chain. First of all, Set up different roles for the nodes in the cluster, assign different permissions to the nodes according to different roles, and design dynamic access to the network mechanism for nodes with different permissions. Secondly, in the election of production nodes, a voting mechanism and an FTS tree based on reputation are designed. The combined election algorithm ensures the security and fairness of the election. Finally, the PBFT consensus process is optimized in terms of the consensus process, and the network overhead in the PBFT consensus is reduced. The experimental results show that the proposed POC consensus algorithm is compared with PBFT The algorithm has the characteristics of high dynamics, election security, and low overhead.